1999
DOI: 10.1029/1999jb900241
|View full text |Cite
|
Sign up to set email alerts
|

Linear ridge groups: Evidence for tensional cracking in the Pacific Plate

Abstract: Abstract. A new class of oceanic bathymetric i•ature, discovered in 1987, consists of en-echelon groups of linear ridges. There are now at least three such sets of ridges known, and their remarkable similarity supports the notion that they result from a widespread tectonic process taking place in the interior of plates. In two of these major linear ridge groups, the Crossgrain and Puka Puka ridges, numerous morphologic features indicate that they originated as tension cracks. The form of the individual volcani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…1), which are perpendicular to the East Pacific Rise in the south Pacific (EPR in Fig. 1), their easterly age progression, which is faster than that of the Hawaiian chain (Sandwell et al, 1995), and their relationship to adjacent gravity lineaments observed from satellites (Sandwell et al, 1995;Lynch, 1999;Sandwell and Fialko, 2004).…”
Section: Tension Resulting From Lithospheric Coolingmentioning
confidence: 97%
See 2 more Smart Citations
“…1), which are perpendicular to the East Pacific Rise in the south Pacific (EPR in Fig. 1), their easterly age progression, which is faster than that of the Hawaiian chain (Sandwell et al, 1995), and their relationship to adjacent gravity lineaments observed from satellites (Sandwell et al, 1995;Lynch, 1999;Sandwell and Fialko, 2004).…”
Section: Tension Resulting From Lithospheric Coolingmentioning
confidence: 97%
“…The westnorthwest cross-trend ridges date from ca. 70 Ma (Davis et al, 2002), and are parallel to the much younger, clearly nonplume Pukapuka ridges (Sandwell et al, 1995;Lynch, 1999, Janney et al, 2000 and to the current direction of Pacific plate motion. Samples Davis et al (2002).…”
Section: Nonplume Attributes Of Seamount Volcanism In the Pacific Primentioning
confidence: 94%
See 1 more Smart Citation
“…A few authors (Smith, 1993;Smith and Lewis, 1999;Anderson, 2000;Janney et al, 2000;Green et al, 2001), argued against the deep mantle plume paradigm (e.g., Schubert et al, 2001). Some authors also propose crack propagation in the lithosphere along hotspot tracks as the reason for Pacific intraplate magmatism (Winterer and Sandwell, 1987;Sandwell et al, 1995;Lynch, 1999). Moreover, some seismic tomography results do not show lowered velocity beneath the Hawaiian hotspot (Wolfe et al, 2002;Foulger et al, 2003).…”
Section: Introductionmentioning
confidence: 90%
“…This evidence casts doubt on both the notion of absolute plate motions computed in the hotspot reference frame, and the nature of the magmatism itself. Different models have been proposed on the origin of these magmatic overproductions, such as deep plume, or alternatively, shallow plumes generated by cracks, or boudins of the lithosphere (Winterer and Sandwell, 1987;Sandwell et al, 1995;Lynch, 1999;Natland and Winterer, 2003). Compositional heterogeneity in the mantle has also been invoked, particularly because no significant positive thermal anomaly relative to normal mid-ocean ridge has been observed (e.g., Stein, 1992, 1993).…”
Section: Asthenospheric Source Of Pacific Hotspots and Westward Driftmentioning
confidence: 98%